Acute Onset of Abdominal Muscle Dyskinesia ("Belly Dancer Syndrome") From Quetiapine Exposure: A Case Report. Issue 2 (March 2018) - Yeh, Jia-Yin; Tu, Kun-Yu; Tseng, Ping-Tao; Lee, Yu; Lin, Pao-Yen
Abstract : Abstract: Belly dancer syndrome, also called belly dance syndrome or belly dancer dyskinesia, is a kind of abdominal dyskinesia with painful sensation. Its etiology is still unclear and there are few studies reporting its association with antipsychotics. Quetiapine is an atypical antipsychotic that causes lower risk of extrapyramidal symptoms than typical antipsychotics. Here, we presented the first case of belly dancer syndrome in a 71-year-old woman with major depressive disorder after short-term use of quetiapine.